2017
DOI: 10.3390/ijms18102020
|View full text |Cite
|
Sign up to set email alerts
|

The Innate and Adaptive Immune System as Targets for Biologic Therapies in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is an immune-mediated inflammatory condition causing inflammation of gastrointestinal and systemic cells, with an increasing prevalence worldwide. Many factors are known to trigger and maintain inflammation in IBD including the innate and adaptive immune systems, genetics, the gastrointestinal microbiome and several environmental factors. Our knowledge of the involvement of the immune system in the pathophysiology of IBD has advanced rapidly over the last two decades, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 168 publications
0
53
0
2
Order By: Relevance
“…In IBD, the mucosal immune response is initiated by the interaction among activated intestinal epithelium, infiltrated innate myeloid cells, and antigens 33 . By immuno‐histochemistry and immunofluorescence staining with CD11b, F4/80 or CD68 and MPO, we found that large number of monocytes, macrophages and neutrophils were recruited to intestinal lesion site in vehicle mice (Figure 2B,C).…”
Section: Resultsmentioning
confidence: 92%
“…In IBD, the mucosal immune response is initiated by the interaction among activated intestinal epithelium, infiltrated innate myeloid cells, and antigens 33 . By immuno‐histochemistry and immunofluorescence staining with CD11b, F4/80 or CD68 and MPO, we found that large number of monocytes, macrophages and neutrophils were recruited to intestinal lesion site in vehicle mice (Figure 2B,C).…”
Section: Resultsmentioning
confidence: 92%
“…Likewise, the role of the binomial composed by the innate and adaptive immune system in IBD therapies involves dozens of feedback loops invoking and sustaining chronic inflammation. However, how the immune system sparks a particular response to repel an IBD threat remains confusing, though it is thought to be immune and non-immune based, with an accepted role of the gut microbiota and non-immune derived cells of the inflammatory cascade including chemokines and inflammasomes (23). In this case, the multifaceted information process limits the repertoire of the immunological machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, 3 other anti-TNF agents have been approved for IBD; adalimumab, certolizumab pegol, and golimumab [200]. Beyond anti-TNF agents, many other biological therapies against proinflammatory ILs, such as ustekinumab, intracellular signaling targets, such as Janus kinase inhibitors (tofacitinib, filgotinib, and upadacitinib), and cell adhesion molecules, such as natalizumab, vedolizumab, etrolizumab, AJM300 and PF-00547659 either have been approved for IBD treatment or are currently under investigation in clinical trials [200][201][202][203][204].…”
Section: From Systems Biology To Treating Ibdmentioning
confidence: 99%